Tree density and forest stratification shape ant assemblages in Brazilian Pantanal forest patches - Oliveira-Santos, L. G. R.; Antoniazzi, R.; Loyola, R.; Vargas, A. B. (International journal of tropical insect science, 2022)
Both forest stratification and habitat characteristics interact dynamically, affecting arthropod distribution in tropical forests. Ants are highly diverse and abundant organisms that occupy several microhabitats in tropical forests. Here, we evaluated how habitat structure (vertical forest stratification, tree and shrub height, tree and shrub density, canopy cover, density of terrestrial Bromeliads) affects ant assemblages in forest patches of the Brazilian Pantanal, one of the largest flooded areas in the world. We captured 57 ant species on the ground and 30 in the canopy of ten forest patches using 160 pitfall traps baited with tuna for each vertical stratum, 320 in total. We found that the ant species composition was different between vertical strata and the ground assemblage was more homogenous than the canopy assemblage. Only forest vertical stratification and tree density were determinants in shaping ant species composition among all habitat structure characteristics based on an RDA analysis. Also, the sympatric congeneric species, belonging to Pseudomyrmex , Camponotus , and Crematogaster , use the vertical strata differently from each other, being species-related. We found higher homogeneity in ant assemblages inhabiting the ground stratum, which can be related to the higher dispersal ability of ground-dwelling than arboreal-dwelling across forest patches. Also, tree density raises as an essential factor shaping ant species composition, probably related to increased resource availability and habitat heterogeneity on forest patches provided by trees. Our findings revealed that trees are critical elements structuring ant communities in forest islands surrounded by a matrix of fields subject to flooding. In this sense, the maintenance of trees supports a comprehensive ant community in forest patches.